Women as Policy Makers: Evidence from a Randomized Experiment - Esther Duflo & Raghabendra Chattopadhyay (BREAD Working Paper No. 001, 2003)
This paper uses political reservations for women in India to study the impact of women's leadership on policy decisions. In 1998, one third of all leadership positions of Village Councils in West Bengal were randomly selected to be reserved for a woman: in these councils only women could be elected to the position of head. Village Councils are responsible for the provision of many local public goods in rural areas. Using a data set we collected on 165 Village Councils, we compare the type of public goods provided in reserved and unreserved Villages Councils. We show that women invest more in infrastructure that is directly relevant to the needs of rural women (water, fuel, and roads), while men invest more in education. Women are more likely to participate in the policy-making process if the leader of their village council is a woman.